Spectral properties of four-time fermionic Green's functions - Shvaika, A.M. (Condensed Matter Physics, 2016)
The spectral relations for the four-time fermionic Green’s functions are derived in the most general case. The
terms which correspond to the zero-frequency anomalies, known before only for the bosonic Green’s functions,
are separated and their connection with the second cumulants of the Boltzmann distribution function is elucidated. The high-frequency expansions of the four-time fermionic Green’s functions are provided for different
directions in the frequency space Отримано в найбiльш загальнiй формi спектральнi спiввiдношення для чотиричасових фермiонних функцiй Ґрiна. Видiлено аномальнi внески на нульовiй частотi, якi ранiше були вiдомi тiльки для бозонних
функцiй Ґрiна, та висвiтлено їхнiй зв’язок з другими кумулянтами функцiї розподiлу Больцмана. Приведено високочастотнi розклади чотиричасових фермiонних функцiй Ґрiна для рiзних напрямкiв в просторi
частот.